PENGUATAN KAPASITAS PENGELOLA BANK SAMPAH LOHJINAWI MELALUI PELATIHAN DAN PEMBUATAN PAVING BLOCK DARI SAMPAH PLASTIK - Fitroh Anugrah Kusuma Yudha; Totok Suwanda; Ahmad Janan Febrianto; Nur Ardiyansyah; Aditya Kurniawan (LPPM Universitas Bina Bangsa, 2023)
The Lohjinawi Garbage Bank is a waste management institution in Indonesia that aims to reduce the amount of waste that ends up in landfills. The Lohjinawi Garbage Bank has been operating for several years, but still needs the strengthening of its management capacity. One way to strengthen the management capacity of the Lohjinawi Garbage Bank is through training and making paving blocks from plastic waste. Training will be conducted for the management and members of the Lohjinawi Garbage Bank in terms of sorting and processing plastic waste into raw materials for paving blocks. This training will provide an understanding of techniques and processes for processing plastic waste, as well as techniques for making quality paving blocks. In addition, the training will also provide an understanding of the marketing and management of the paving block business. After the training, paving blocks were made from processed plastic waste. The resulting paving blocks will be used to build parking areas and roads around the Lohjinawi Garbage Bank environment. Apart from that, paving blocks can also be sold to increase the income of the Lohjinawi Garbage Bank. With training and making paving blocks from plastic waste, it is hoped that the Lohjinawi Garbage Bank can strengthen its management capacity and increase its business income. In addition, using paving blocks made from plastic waste can also reduce the amount of plastic waste that ends up in landfills and reduce the use of conventional building materials that are not environmentally friendly